O desenvolvimento profissional do professor de educação básica em grupos de pesquisa - Cruz, Vanessa Alves de Almeida (2017)
This research aims to understand the process of professional development of Basic Education teachers, inserted in a research group. This qualitative and interpretative study was carried out with four elementary education teachers who belong to the Group of Studies and Research on Formative and Educational Practices in Mathematics (GEPRAEM), Federal University of São Carlos (UFSCar), Sorocaba campus - SP. Data construction used group documents such as: schedules, meetings meetings, research reports, and teacher productions. To deepen the data, audio recordings of face-to-face meetings and semi-structured interviews were conducted with the four participating Basic Education teachers. The analysis used the data triangulation technique, using the theoretical framework on professional development (CHRISTOPHER DAY, 1999 AND 2005, MARCELO AND VAILLANT (2009 AND 2012), and research professor (ANDRÉ, 2001; DINIZ, 2006). Indicate that the practices experienced by the teachers in the research group, such as elaboration of narratives, research projects, scientific articles and reports of experience, participation in events, reading and discussion of theoretical and methodological references, generate individual and collective learning, such as Collaborative attitudes, reflection and investigation of the practice, academic literacy, participation in events, to understand an object from multiple perspectives, to see itself as a researcher, composing a process of professional development in a teacher training with investigative posture.